2024
DOI: 10.61298/rans.2024.2.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of aeromagnetic data over parts of Southwestern Nigeria

Emmanuel Ike,
Adetola Sunday Oniku,
Sabastine Chinedu Ezike
et al.

Abstract: This study endeavors to assess spectral depths, explore Basement structure variability, and deduce geothermal heat distribution by determining Curie point depth (Zb) through aeromagnetic data analysis across 14 sheets in Southwestern Nigeria. The depths to the shallow magnetic source (Zt) range from 0.14286 km to 1.02632 km, indicating sediment thickness, with the deepest point situated in the Northwestern region and progressively shallower towards the central and Southern portions of the study area. Depths to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 23 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…The above result agrees with the conclusion by Ref. [14] that sedimentary rocks have rather low magnetic intensity, the observed intensity over them is largely due to igneous or metamorphic basement rocks or sedimentary rocks with banded iron formations. Studies in recent past [23,24,[30][31][32] have shown that depth to the magnetic sources are largely dependent on the geological composition of the subsurface.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The above result agrees with the conclusion by Ref. [14] that sedimentary rocks have rather low magnetic intensity, the observed intensity over them is largely due to igneous or metamorphic basement rocks or sedimentary rocks with banded iron formations. Studies in recent past [23,24,[30][31][32] have shown that depth to the magnetic sources are largely dependent on the geological composition of the subsurface.…”
Section: Discussionsupporting
confidence: 92%
“…where negative magnetic anomalies were recorded (sedimentary basin area), probably because of the presence of schist. The closures of magnetic low are mostly in areas with thick sedimentary cover whereas closures of the magnetic high are probably due to shallow basements, due to thin sedimentary cover or basic intrusion into the igneous and metamorphic basement rocks [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations